If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -1.6x = -1.6(-4x + 1) Reorder the terms: 13 + -1.6x = -1.6(1 + -4x) 13 + -1.6x = (1 * -1.6 + -4x * -1.6) 13 + -1.6x = (-1.6 + 6.4x) Solving 13 + -1.6x = -1.6 + 6.4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6.4x' to each side of the equation. 13 + -1.6x + -6.4x = -1.6 + 6.4x + -6.4x Combine like terms: -1.6x + -6.4x = -8x 13 + -8x = -1.6 + 6.4x + -6.4x Combine like terms: 6.4x + -6.4x = 0.0 13 + -8x = -1.6 + 0.0 13 + -8x = -1.6 Add '-13' to each side of the equation. 13 + -13 + -8x = -1.6 + -13 Combine like terms: 13 + -13 = 0 0 + -8x = -1.6 + -13 -8x = -1.6 + -13 Combine like terms: -1.6 + -13 = -14.6 -8x = -14.6 Divide each side by '-8'. x = 1.825 Simplifying x = 1.825
| 0.14(y-1)+0.08y=0.16y-0.01(20) | | 5a+30x= | | y+3/5=2y+1/5 | | 7a+10-5a=4+6-14a | | 3/x-2/3=7/3 | | 4.5-2p+10/3p | | 24+h=180 | | 2+4n=7n+5 | | (85x-51y)-(60x+21y)= | | -3x+2=8-6(2-x) | | 5+4x^2=85 | | 1/4y-3=5-2u | | 9-9=1 | | 14n/3-2(-1/5+10n/3)=-13/5 | | 2(x+3)(x+3)=40 | | (48x+53y)-(-41x+16y)= | | 3X+4+5x+2=180 | | 9/9-8=9 | | 0.20x+0.15(50)=24.5 | | 27-2(-4)= | | 3(x-4)=4(4-x) | | 2x*3y=18 | | 100b^2+180+81=0 | | 4.3x+3-6.3x=1 | | t=12x+3 | | (39x-21y)+(42x+50y)= | | -(4+3k)=-28+5k | | 4x-27.3=x | | (55x+58y)-(-31x+11y)= | | B=9/10 | | 4x+5=-34 | | 10.5/2.8 |